Anti-Nazism and the Fear of Pronatalism in the American Popular Front. (December 2016) - Lynn, Denise
Abstract : Women in the American Communist Party believed the rise of fascism in Europe was a direct threat to women's rights. Hitler's rise to power and what Communists read as a push to 'nationalize' German women's maternity compelled Communist women to argue that fascism was a threat to women's rights and perpetuated false ideals of 'natural' gender roles. Communist women dutifully followed the party's anti-fascist line; however, they expanded it by arguing that gender inequality was on the rise in fascist nations and women's rights had to move to the forefront of Popular Front struggles. Communists emphasized the rights of mothers and workers in an effort to better secure the rights of women. This article argues that party women rejected Nazi pronatalism, advanced women's rights within the party's 'United Front' and pushed their agenda within the American Communist Party.